The Impact of Parental Involvement on Student Academic Performance and School Administration Efficacy in Enhancing Educational Outcomes - Nasir, Nasir; Kadri, Dzul; Akbar, Rahmat (Educia Journal, 2023)
This study seeks to establish how parents influence students’ academic achievement as well as the efficiency of school administration with the purpose of narrowing the gaps in the current literature concerning both the mediators of the relationships between parental engagement and results, as well as the moderating variables. Using a quantitative research strategy, a sampling of 500 parents, educators and school officials completed standardized questionnaires. The findings describe a positive relationship between parental involvement and students’ academic achievement and the perception of the school’s administration efficiency. In more detail, enhanced parental involvement was connected with increased students’ performance and effective school management. The study also reveals that parental involvement affects the performance of students directly controlling all other factors including school administration. This draws attention to the genuine and significant contribution of parental involvement in improving student performance which has not been given much emphasis in prior research chiefly couched in general benefits. The study also confirms that the role of parental involvement is to provide insulation to academic performance since the social economic inequalities are likely to have negative effects on the performance of the student. This work also supports context-based intervention approaches that successfully promote appropriate parental involvement efforts; in the cultures or regions where parents of the learners have language barriers or other forms of hardship. In this way, the research provides important knowledge for educators, policymakers and researchers targeting at increasing educational equity and school effectiveness.